Identification of BCL-XL as highly active survival factor and promising therapeutic target in colorectal cancer - Scherr, Anna-Lena; Mock, Andreas; Gdynia, Georg; Schmitt, Nathalie; Heilig, Christoph E.; Korell, Felix; Rhadakrishnan, Praveen; Hoffmeister-Wittmann, Paula; Metzeler, Klaus H.; Schulze-Osthoff, Klaus; Illert, Anna Lena; Börries, Melanie; et al. (Cell death & disease, 2020)
Since metastatic colorectal cancer (CRC) is a leading cause of cancer-related death, therapeutic approaches overcoming primary and acquired therapy resistance are an urgent medical need. In this study, the efficacy and toxicity of high-affinity inhibitors targeting antiapoptotic BCL-2 proteins (BCL-2, BCL-XL, and MCL-1) were evaluated. By RNA sequencing analysis of a pan-cancer cohort comprising >1500 patients and subsequent prediction of protein activity, BCL-XL was identified as the only antiapoptotic BCL-2 protein that is overactivated in CRC. Consistently, pharmacologic and genetic inhibition of BCL-XL induced apoptosis in human CRC cell lines. In a combined treatment approach, targeting BCL-XL augmented the efficacy of chemotherapy in vitro, in a murine CRC model, and in human ex vivo derived CRC tissue cultures. Collectively, these data show that targeting of BCL-XL is efficient and safe in preclinical CRC models, observations that pave the way for clinical translation.